A perspective on flotation: a review - Peleka, Efrosyni N; Gallios, George P; Matis, Kostas A (Journal of chemical technology and biotechnology (1986), 2018)
The problem of fine particles processing has become important both in mineral processing and also for water and wastewater engineering. It is accepted, on the other hand, that the bubble–particle collection efficiency increases with decreasing bubble size. A decrease in bubble size can be obtained using different methods (dispersed‐air, where electroflotation is included, and/or dissolved‐air flotation), as discussed. Following an introduction of the subject, older laboratory results are presented in this review paper (based on 4 decades of experience), explaining the above, giving further ideas and possibly, assisting future researchers in the area. Examples given are: separation of fine mineral particles (such as pyrite and magnesite), and of metal ions (as chromium, arsenic, copper, zinc, germanium and so on); among the various available techniques, mention is given to ion, precipitate, adsorbing colloid, sorptive and biosorptive flotation ‐ including certain comparisons for the same application. The metal ion flotation application deserves further study and work, mainly for selective removal. © 2017 Society of Chemical Industry